2010
DOI: 10.1091/mbc.e09-07-0601
|View full text |Cite
|
Sign up to set email alerts
|

Poleward Transport of TPX2 in the Mammalian Mitotic Spindle Requires Dynein, Eg5, and Microtubule Flux

Abstract: TPX2 is a spindle assembly factor that is required for MT assembly near chromosomes. Using photoactivation of fluorescence, we report that TPX2 is transported poleward in the half-spindle. Poleward transport of TPX2 is sensitive to inhibition of dynein or Eg5, and to suppression of MT flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 47 publications
4
88
1
Order By: Relevance
“…Human U2OS 14 11 0.5 SL-13.3 (Ganem et al 2005) and 15.4 (Arnaoutov et al 2005); MD-12 (Arnaoutov et al 2005) and 9.4 (Tedeschi et al 2007);and F-0.53 (Ganem et al 2005) and 0.53 (Maffini et al 2009) (Ma et al 2010); MD-13 (our unpublished observations); and F-1.37 (Ferenz and Wadsworth 2007) and 0.96 (Ma et al 2010) 1.7…”
Section: A Relation Between Flux Velocity Spindle Size and Metaphasementioning
confidence: 59%
“…Human U2OS 14 11 0.5 SL-13.3 (Ganem et al 2005) and 15.4 (Arnaoutov et al 2005); MD-12 (Arnaoutov et al 2005) and 9.4 (Tedeschi et al 2007);and F-0.53 (Ganem et al 2005) and 0.53 (Maffini et al 2009) (Ma et al 2010); MD-13 (our unpublished observations); and F-1.37 (Ferenz and Wadsworth 2007) and 0.96 (Ma et al 2010) 1.7…”
Section: A Relation Between Flux Velocity Spindle Size and Metaphasementioning
confidence: 59%
“…However, the interaction of TPX2 with microtubules in cells is dynamic, as evidenced by its poleward motion in the spindle (9). One possibility that can account for these differences is that modifications, such as phosphorylation, or interactions with other binding partners, such as dynein, regulate TPX2 dynamic behavior in cells.…”
Section: Discussionmentioning
confidence: 99%
“…During spindle formation, TPX2 is required for microtubule formation near kinetochores, an activity that requires GTP-bound Ran, which relieves the inhibitory action of importin ␣/␤ on TPX2 (8). In addition, it has been demonstrated that the C terminus of TPX2 binds to the bipolar kinesin Eg5 and targets the motor to spindle microtubules (9,10). Expression of TPX2 lacking the C-terminal 35 amino acids, which contribute to Eg5 binding, results in defective spindles with greatly reduced Eg5 on spindle microtubules, unfocussed spindle poles, and bent and buckled microtubules (11).…”
mentioning
confidence: 99%
“…Tpx2 interacts with several molecules, including the kinase Aurora A (6-8), the microtubule-sliding kinesin Eg5 (25,26), and the plus-end directed kinesin Hklp2/Kif15 (2, 27). We therefore analyzed the status of these proteins in Tpx2-depleted cells.…”
Section: Tpx2 Is Essential For Chromatin-dependent Microtubule Nucleamentioning
confidence: 99%